Strategi Pengembangan objek Wisata Linjuang melalui Pendekatan Analisis SWOT - Endarwita Endarwita (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze external and internal factors in the form of strengths, weaknesses, opportunities and threats in the development of Linjuang tourism objects in Lubuk Sikaping, Pasaman Regency, West Sumatra. After the analysis is carried out, a development strategy is formulated by minimizing weaknesses and threats and then maximizing the existing strengths and opportunities. This study uses a descriptive qualitative research method using SWOT analysis tools (Strengths, Weaknes, Opportunities, Threats). Data collection techniques through literature study, observation and interviews with owners, communities and visitors of Linjuang tourism objects. Based on the results of the study, it is concluded that the strategy for developing Linjuang tourism objects, among others, is by completing facilities and markets such as toilets, prayer rooms and parking locations as well as maintenance of tourist attraction areas, then promoting tourism objects through online and print media and involving the government, private sector and the community in management. tourist attraction. Keywords: Development Strategy; SWOT Analysis; Tourism